No. 1 Mine Remembered - Stonebanks, Roger (Labour / Le Travail, 2000)
Discusses the unveiling of a plaque on 26 June 1999 at the site of No. 1 Mine in Nanaimo, B.C., where coal was mined from 1883 to 1938. The No. 1 Mine disaster in 1887 was the worst in British Columbia's history.